Molecular and sociocultural exploration of sourdough: impacts on gluten sensitivity and bread characteristics - Clark, Caitlin, author; Van Buiten, Charlene, advisor; Stone, Martha, committee member; Weir, Tiffany, committee member; Gentile, Chris, committee member; Prenni, Jessica, committee member (Colorado State University. Libraries, 2023)
Sourdough is a bread product fermented by communities of wild bacteria and fungi known as a starter culture. Previous work has examined the effects of specific starter organisms on bread quality, but the relationships between whole microbiomes and dough/bread physicochemical properties are currently unknown. The objective of this study was to investigate the relationship between physicochemical properties of sourdough breads and the microbiomes of their starter cultures. Twenty sourdough starters with characterized microbiomes were used to produce wheat-based dough and bread. The chemical properties (pH, titratable acidity, free amino acids, Aw) of dough and physical properties (loaf volume, crust color, texture) of the breads were compared to a control fermented with baker's yeast. The degradation and toxicity of gliadin resulting from fermentation with the sourdough samples was also studied in vitro. Results indicate that sourdough-fermented breads produced under real-world conditions are distinct from yeast-fermented bread in terms of physicochemical parameters and proteolysis, which may exert downstream effects on the inflammatory capacity of gluten. We also investigated the beliefs and behaviors of gluten-sensitive sourdough consumers and professional sourdough bakers. We found that commercial sourdough is not reported to relieve gluten-mediated symptoms for consumers diagnosed with celiac disease (CD) or non-celiac gluten sensitivity (NCGS), but undiagnosed (UD) gluten-sensitive consumers may benefit from it. We also determined that sourdough bakers act as brokers of health advice in the gluten-sensitive community.
Keywords: fermentation; gluten; sourdough; gliadin; celiac; microbiome